Investigating faculty-based communities of practice for technology-augmented pedagogical practices at Eduardo Mondlane University: A case of innovators and adopters - Miguel, Elódia Júlia da Graça (School of Education, 2023)
Institutional inhibiting factors, and lack of motivation and support at the University of Eduardo Mondlane (UEM) result in lecturers not teaching using technology-augmented approaches. This research study investigates how a faculty-based EdTech-UEM professional development model could potentially foster Communities of Practice (CoPs) for technology-augmented pedagogical practices in UEM faculties. One way of addressing the technology-augmented pedagogical practices is to understand motivations, pedagogical practices, support and barriers of lecturers to adopt them. Lecturers (innovators and adopters: early adopters and late majority adopters) who participated in the four workshops on EdTech professional development, reported instances of innovators exhibiting peer leadership in group-learning activities during the workshops. The CoPs theoretical framework was used to investigate social learning and support among the innovators and adopters. After the workshops, which coincided with the beginning of the pandemic, 18 lecturer participants of the workshops were purposefully selected, and semi-structured interviews were conducted with the goal of better understanding the support needs among lecturers (innovators and adopters) after the workshops as well as discussing the best ways to overcome potential barriers and challenges in technology-augmented pedagogical practices and provide a conducive environment for the emergence of CoPs in the adoption of technology-augmented pedagogical practices. The workshops were before the pandemic and lecturers implemented what they learnt during the pandemic. It was serendipitous as the workshops helped them to prepare for ERT even it was not the aim of the initiative that completed before the pandemic started. The interviews were recorded and transcribed, and the empirical data was analysed through an interpretive approach. The interpretive method looks at how people make sense of their experiences, as well as how they construct and attribute meaning to their worlds. The result of the interpretive analysis was based on the description of qualitative themes formed and related from each other in multiple case studies of both innovators and adopters. The anonymity of their responses was guaranteed.